Study guides

Q: What is m -6?

Write your answer...

Submit

Related questions

m, m+6, m+12

Sun of 6 and m

m + 6 m + 12

If: -6+m = 0 Then: m = 6

The average of 6, 15 and m is (6 + 15 + m) / 3 = (21 + m)/3 = 7 + m/3

It is 72m.

6 + m = 16 m = 16 - 6 = 10

A Giraffe is 6 m tall and a elephant

(m + 6)(m + 1)

6 m is 6 meters and it is bigger.

1 km = 1000 m 6 km = 6*1000 = 6000 m Hence 6 km is equal to 6000 m

1 km = 1000 m so 6 km = 6*1000 = 6000 m. Simple!

m/-6 + 6 = 41 subtract 6 from each side m/-6 = 35 multiply both sides by -6 m = -210

m+6n

m/6 is an algebraic term

21 m 6 cm

The equation for n layers is S(n) = n(n+1)(2n+1)/6It is simplest to prove it by induction.When n = 1,S(1) = 1*(1+1)(2*1+1)/6 = 1*2*3/6 = 1.Thus the formula is true for n = 1.Suppose it is true for n = m. That is, for a pyramid of m levels,S(m) = m*(m+1)*(2m+1)/6Then the (m+1)th level has (m+1)*(m+1) oranges and soS(m+1) = S(m) + (m+1)*(m+1)= m*(m+1)*(2m+1)/6 + (m+1)*(m+1)= (m+1)/6*[m*(2m+1) + 6(m+1)]= (m+1)/6*[2m^2 + m + 6m + 6]= (m+1)/6*[2m^2 + 7m + 6]= (m+1)/6*(m+2)*(2m+3)= (m+1)*(m+2)*(2m+3)/6= [(m+1)]*[(m+1)+1)]*[2*(m+1)+1]/6Thus, if the formula is true for n = m, then it is true for n = m+1.Therefore, since it is true for n =1 it is true for all positive integers.

42

Perimeter of rectangle: 2*(7+6) = 26 m

5/6 - m/4 = 1/3. First isolate the variable m, start by adding m/4 to both sides. 5/6 = 1/3 + m/4. Then subtract 1/3 from each side. 5/6 - 1/3 = m/4. Next multiply both sides by 4. 4 ( 5/6 - 1/3 ) = m. Then solve for m. 4 ( 5/6 - 2/6 ) = m. 4 ( 3/6 ) = m 4 ( 1/2 ) = m 2 = m

m(m - 6) = 91 m(m) + m(-6) = 91 m2 - 6m = 91 subtract 91 from both sides m2 - 6m - 91 = 0 since -91 = (-13)(7) and -13 + 7 = -6, then (m + 7)(m - 13) = 0 m + 7 = 0 or m - 13 = 0 m = -7 or m = 13

m - 8 + 143 - 5the answer is m+130

17 + 6 + m

The value is 6 more than whatever ' m ' is.

11